The Object of Sexual Desire: Examining the "What" in "What Do You Desire?". (18th August 2014) - Mark, Kristen; Herbenick, Debby; Fortenberry, Dennis; Sanders, Stephanie; Reece, Michael
Abstract Introduction Over the past two decades, sexual desire and desire discrepancy have become more frequently studied as have potential pharmaceutical interventions to treat low sexual desire. However, the complexities of sexual desire—including what exactly is desired—remain poorly understood. Aims To understand the object of men's and women's sexual desire, evaluate gender differences and similarities in the object of desire, and examine the impact of object of desire discrepancies on overall desire for partner in men and women in the context of long‐term relationships. Methods A total of 406 individuals, 203 men and 203 women in a relationship with one another, completed an online survey on sexual desire. Main Outcome Measures Reports of the object of sexual desire in addition to measures of sexual desire for current partner were collected from both members of the couple. Results There were significant gender differences in the object of sexual desire. Men were significantly more likely to endorse desire for sexual release, orgasm, and pleasing their partner than were women. Women were significantly more likely to endorse desire for intimacy, emotional closeness, love, and feeling sexually desirable than men. Discrepancies within the couple with regard to object of desire were related to their level of sexual desire for partner, accounting for 17% of variance in men's desire and 37% of variance in women's desire. Conclusions This research provides insights into the conceptualization of sexual desire in long‐term relationships and the multifaceted nature of sexual desire that may aid in more focused ways to maintain desire over long‐term relationships. Future research on the utility of this perspective of sexual desire and implications for clinicians working with couples struggling with low sexual desire in their relationships is discussed. Mark K, Herbenick D, Fortenberry D, Sanders S, and Reece M. The object of sexual desire: Examining the "what" in "what do you desire?" J Sex Med 2014;11:2709–2719.